Impact of Comorbidities on the Severity of Disease & Outcome in Children with COVID 19 at a Tertiary Care Pediatric Hospital, Rawalpindi. - Rai Muhammad Asghar; Muddassar Sharif; Khalid Saheel; Isfandyar Khan; Abid Hussain; Rai Rijjal Ashraf (Journal of Rawalpindi Medical College)
Introduction: Coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was initially identified in Wuhan, China, in December 2019. The virus affects almost all countries of the world. It has infected humans in all age groups, of all ethnicities, both males and females. It is considered that COVID-19, in those with underlying health conditions or co-morbidities, has an increasingly rapid and severe progression, often leading to death. This study is designed to evaluate the impact of co-morbidities on the severity and outcome of COVID-19 infection in children.